2003
DOI: 10.1002/hed.10363
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values for aspiration after endoscopic laser resections of malignant tumors of the hypopharynx and larynx

Abstract: Background. CO 2 -laser surgery is a relatively new treatment for selected carcinomas of the upper aerodigestive tract. The purpose of our study was to evaluate prospectively the functional results for swallowing after C0 2 -laser resections.Methods. The sample was composed of 210 consecutive patients with malignancies of the larynx and hypopharynx treated with CO 2 laser between February 1998 and January 2002. Endoscopic resections included all T1 and T2 tumors and selected T3 and T4 tumors. T1 glottic tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 32 publications
0
37
1
4
Order By: Relevance
“…However, endoscopy techniques (i.e., endoscopic laser resection) have been used only in a few institutions, and the indication for these treatments is unclear (9,11). Although Shimizu et al (9) performed endoscopic submucosal dissection in 4 patients with early-stage HPC and reported no local recurrences, no distant metastasis, and no early or late complications, Bernal-Sprekelsen et al (11) performed endoscopic resection using a CO 2 laser and reported the need for a nasogastric feeding tube in 23.2% of the patients with small tumors, postoperative pneumonia in 5.7%, temporary postoperative coughing during oral intake in 28.1%, and severe swallowing difficulties in 3.8%. Thus, the factors associated with the occurrence and severity of various complications after endoscopic resection remain to be clarified (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopy techniques (i.e., endoscopic laser resection) have been used only in a few institutions, and the indication for these treatments is unclear (9,11). Although Shimizu et al (9) performed endoscopic submucosal dissection in 4 patients with early-stage HPC and reported no local recurrences, no distant metastasis, and no early or late complications, Bernal-Sprekelsen et al (11) performed endoscopic resection using a CO 2 laser and reported the need for a nasogastric feeding tube in 23.2% of the patients with small tumors, postoperative pneumonia in 5.7%, temporary postoperative coughing during oral intake in 28.1%, and severe swallowing difficulties in 3.8%. Thus, the factors associated with the occurrence and severity of various complications after endoscopic resection remain to be clarified (9).…”
Section: Discussionmentioning
confidence: 99%
“…In attempt to decrease the treatment-related morbidities and to increase post-operative quality of life, minimally invasive surgery such as transoral LASER microsurgery has been investigated for its potential use in hypopharyngeal cancer [59][60][61]. With the recent advancement and increasing use of robotic assisted surgery in otolaryngology [62][63][64][65], there are reports on the potential value of transoral robotic surgery (TORS) for the management of tumors of the upper aerodigestive tract [66][67][68].…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Aspiration pneumonia is related to the extension of tissue resection [23]. In a recent study on complications linked to TLM, the rate of severe bleedings (needing either, revision surgery, intensive care unit observation, and/or blood transfusion) was found to be of 8 % in the first series and of 5.9 % after a longer period of experience with TLM [17].…”
Section: Discussionmentioning
confidence: 94%